Roles of Bacterial Symbionts in Transmission of Plant Virus by Hemipteran Vectors - Wu, Wei; Shan, Hong-Wei; Li, Jun-Min; Zhang, Chuan-Xi; Chen, Jian-Ping; Mao, Qianzhuo (Frontiers in Microbiology, 2022)
The majority of plant viruses are transmitted by hemipteran insects. Bacterial symbionts in hemipteran hosts have a significant impact on the host life, physiology and ecology. Recently, the involvement of bacterial symbionts in hemipteran vector-virus and vector-plant interactions has been documented. Thus, the exploitation and manipulation of bacterial symbionts have great potential for plant viral disease control. Herein, we review the studies performed on the impact of symbiotic bacteria on plant virus transmission, including insect-bacterial symbiont associations, the role of these bacterial symbionts in viral acquisition, stability and release during viral circulation in insect bodies, and in viral vertical transmission. Besides, we prospect further studies aimed to understand tripartite interactions of the virus-symbiotic microorganisms-insect vector.